Risk-sharing and land misallocation - Davide Pietrobon; Alessandro Ruggieri (Lund University, School of Economics and Management, Department of Economics, 2024)
We study the impact of incomplete consumption risk-sharing on land misallocation in rural economies. We develop a general equilibrium model of land cultivation choices, where heterogeneous agricultural households face idiosyncratic output shocks and insure themselves by participating in a risk-sharing arrangement. Incomplete insurance distorts households' choices, leading them away from maximizing expected incomes and resulting in land misallocation. Using the latest ICRISAT panel data from rural India, we quantify the losses attributable to limited risk-sharing. Completing insurance markets leads to output and welfare gains of 19% and 29%, respectively. Improving the functioning of consumption insurance markets within an otherwise undistorted economy can yield gains comparable to those achieved by removing distortions in factor markets.
Keywords: O11; D61; Q12; D52; 330; Misallocation; risk-sharing; agriculture; productivity; welfare